Noopolitical Aspect of Information Strategies of States - Nikonov, Sergey Borisovich; Baichik, Anna Vitalievna; Puiy, Anatoli Stepanovich; Labush, Nikolai Sergeevich (International Review of Management and Marketing, 2015)
Modern political science assumes that states need a civilized strategy ensuring the progressive development of a society. The leading positions in the global policy have been typically held by the states, which had certain national strategies, including information strategies. In light of the ideas of the need to change Russia's information strategy, which are suggested in the scientific literature, the author proposes to adopt the concept of noopolitics. Noopolitic is an information strategy which involves manipulating international processes by forming, through the media, a positive or negative attitude of the public towards the internal and external policy of a state or a coalition of states, with the view of forming a positive or negative image of ideas and advocated moral values. Keywords: Noopolitics, information strategy, information war JEL Classifications: H11; F51; Z13